An examination on durability and degradation of glass fiber reinforced polymer structures - Syamsir A.; Mohamad D.; Beddu S.; Itam Z.; Sadon S.N. (Mattingley Publishing, 2023)
Corrosion resistance; Degradation; Durability; Glass fibers; Polymers; Reinforcement; Crossarm; Environmental conditions; Glass fiber reinforced polymer; High durability; ITS applications; Lightning impulse; Outdoor environment; Transmission tower; Fiber reinforced plastics